Everolimus precision therapy in NPRL2- and NPRL3-related epilepsy - Carapancea, Evelina; Eklund, Erik A.; Verhelst, Helene; Cilio, Maria Roberta (Epilepsia, 2025)
Disinhibition of the mechanistic target of rapamycin (mTOR) pathway has been observed in patients with loss-of-function variants in the disheveled, Egl-10, and pleckstrin domain-containing protein 5 (DEPDC5), and nitrogen permease regulator-like proteins 2 and 3 (NPRL2, and NPRL3) genes, which encode the components of GTPase activating protein Activity Toward Rags Complex 1 (GATOR1) complex. Everolimus, a synthetic mTOR inhibitor, has shown efficacy in treating seizures in patients with DEPDC5 epilepsy, but seemed to worsen seizures in the one published patient with NPRL3 epilepsy. We studied four patients with NPRL2- and NPRL3-related epilepsies with intractable focal seizures treated with everolimus as add-on therapy. Age at treatment initiation was between 1 month and 26 years; patients had baseline seizure frequencies ranging from 15 to 301 per month and had failed 6–14 antiseizure medications. Daily doses ranged between 3.75 and 11.5 mg with trough levels between 5 and 8.7 ng/mL. Two patients became seizure-free by 2 months of treatment. In one of them, seizures recurred at levels below 4 ng/mL, and seizure freedom was regained with increased levels. The other two patients experienced a clinically meaningful seizure reduction of 52% and 86%, respectively. Two patients experienced stomatitis, resulting in everolimus discontinuation in one; one patient had hyperlipidemia and another had recurrent respiratory infections, which resolved with dose reduction. In conclusion, everolimus add-on may be effective in substantially reducing seizures in patients with NPRL2- and NPRL3-related epilepsies. However, strict surveillance is required, especially in young patients.
Publisher Copyright: © 2025 International League Against Epilepsy.
Keywords: everolimus; GATOR1 complex; mTOR pathway; NPRL2/3-related epilepsy; precision medicine